Incidence and Risk Factors of Hypogonadism in Male Patients With Latent Autoimmune Diabetes and Classic Type 2 Diabetes - Cai, Meili; Cui, Ran; Yang, Peng; Gao, Jingyang; Cheng, Xiaoyun; Sheng, Chunjun; Li, Hong; Sheng, Hui; Qu, Shen; Zhang, Manna (Frontiers in Endocrinology, 2021)
Objectives: This study aimed to compare the prevalence of hypogonadism between male patients with latent autoimmune diabetes (LADA) and type 2 diabetes (T2DM) and investigate the risk factors for hypogonadism in these patients. Methods: This cross-sectional study evaluated 367 male patients with LADA (n=73) and T2DM (n=294) who visited the endocrinology department of Shanghai Tenth People’s Hospital between January 2016 and October 2019 for diabetes management. Sex hormones, lipid profiles, sex hormone-binding globulin (SHBG), glycosylated hemoglobin A1c, beta-cell function, uric acid, and osteocalcin were determined in serum samples. Hypogonadism was defined as calculated free testosterone (cFT) less than 220 pmol/L along with the presence of symptoms (positive ADAM score). Results: The rate of hypogonadism in the LADA and T2DM group were 8.2, and 21.7%, respectively (p=0.017). After adjusting possible confounders, the rate of hypogonadism in the LADA group was comparable to those of the T2DM group. Univariate logistic regressions demonstrated that age, BMI, triglycerides, total cholesterol, uric acid and SHBG were risk factors for hypogonadism in men with diabetes, Especially, age, BMI and SHBG were independent risk for hypogonadism in men with diabetes. `Conclusion: This is the first evidence to explore the rate of hypogonadism in male patients with latent autoimmune diabetes (LADA). In a population of admission to a large urban hospital in China, after adjusting possible confounders, the rate of hypogonadism was comparable to those of the T2DM group, which suggested the association of hypogonadism and the etiology of hyperglycemia was limited in this study.